Poly-L-Lysine and Human Plasmatic Fibronectin Films as Proactive Coatings to Improve Implant Biointegration - Miranda, Anamar; Seyer, Damien; Palomino-Durand, Carla; Morakchi-Goudjil, Houda; Massonie, Mathilde; Agniel, Rémy; Rammal, Hassan; Pauthe, Emmanuel; Gand, Adeline (Frontiers in Bioengineering and Biotechnology, 2022)
The success of stable and long-term implant integration implies both promotion, control and respect of the cell microenvironment at the site of implantation. The key is to enhance the implant-host tissue cross-talk by developing interfacial strategies that guarantee an optimal and stable seal of soft tissue onto the implant, while preventing potential early and late infection. Indeed, implant reject is often jeopardized by lack of stable tissue surrounding the biomaterial combined with infections which reduce the lifespan and increase failure rate of implants, morbidity, and account for high medical costs. Thin films formed by the Layer-by-Layer (LbL) assembly of oppositely charged polyelectrolytes are particularly versatile and attractive for applications involving cell-material contact. With the combination of the extracellular matrix protein Fibronectin (Fn,purified from human plasma) and Poly-L-Lysine (PLL,exhibiting specific chain lengths) we proposed proactive and biomimetic coatings able to guarantee enhanced cell attachment and exhibiting antimicrobial properties. Fn, able to create a biomimetic interface that could enhance cell attachment and promote extracellular cell matrix remodeling, is incorporated as the anionic polymer during film construction by the LbL technic whereas PLL is used as the cationic polymer for its capacity to confer remarkable antibacterial property.